Association of polymorphisms KCNN2 and NOS1AP with sudden cardiac death - P. S. Orlov; D. Е. Ivanoshchuk; А. А. Ivanova; S. К. Malyutina; V. P. Novosyolov; М. I. Voevoda; V. N. Maximov (Российский кардиологический журнал)
Aim. Assessment of the associations of mononucleotide polymorphisms (MNP) of genes: KCNN2 (rs13184658, rs10076582, rs338625) and NOS1AP (rs12567209, rs348624, rs3751284, rs 12143842), with sudden cardiac death (SCD), and evaluation of the clutch units.Material and methods. The study designed as a case-control. Group of males, died SCD (n=278) was formed according with the European Cardiology Society criteria. The controls (n=274), matched by age and gender, was collected from DNA of international research projects MONICA and HAPIEE. Genomic sequencing was done with real time PCR. For inequation assessment of the clutch groups within the MNP pairs, the D’ coefficient was in use. Comparison of the groups by the rates of genotypes and alleles was done with a contingency tables and Chi-square by Pearson. Relative SCD risk was calculated as an odds ratio with Fischer criteria and Chi-square. The differences were noted as significant with p<0,05.Results. For the assessed MNPs gene NOS1AP the following significant differences in genotypes frequencies were found: rs12567209 GG vs AA+AG OR =1,76 (CI 1,07¬2,9) p=0,026, rs3751284 CC vs CC+TT OR =0,68 (CI 0,47-0,97) p=0,037, rs12143842 CC vs CT+TT OR =0,54 (CI 0,38-0,75) p=0,0004. For alleles of the gene NOS1AP the following significant differences were found: rs12567209 A vs G OR =0,58 (CI 0,36¬0,93) p=0,025 and rs12143842 С vs T OR =0,6 (CI 0,46-0,79) p=0,0004. In further assessment it was shown that the loci rs12143842 and rs12567209 are clutched (D’ =1). In evaluation of the clutch block for rs12143842 and rs12567209 the following was found: TG vs CG+CA OR =1,64 (CI 1,25-2,16) p=0,0004.Conclusion. MNPs (rs13184658, rs10076582, rs33862) of the gene KCNN2 and rs348624 gene NOS1AP, probably, does not play role in SCD in Novosibirsk population. rs12143842, rs12567209 and rs3751284 NOS1AP are associated with SCD. Further studies needed to assess rs12143842 and rs3751284 of gene NOS1AP, as the rs12567209 is clutched with rs12143842.